Evaluasi Kapabilitas Proses Timbangan Mesin PengemasanTepung Terigu Menggunakan Sixpack Report PT. ISM Divisi Bogasari Flour Mills - Azrie Sunata; Rizki Achmad Darajatun (Industrika : Jurnal Ilmiah Teknik Industri, 2026)
Quality control in the packaging process plays a vital role in the food industry to ensure that products meet established standards. Inaccurate weighing during packaging can lead to product inconsistency, increased waste, and reduced customer trust. This study aims to evaluate the accuracy and process capability of two packaging machines on the Consumer Pack (CP) Line 2 at PT ISM Bogasari Flour Mills using the Sixpack Report statistical approach through Minitab 22.1 software. Data were collected by direct sampling of 1,000-gram wheat flour products over three days with two speed variations (55 and 60 packs per minute). The results show that all combinations of machines and speeds had Cp, Cpk, Pp, and Ppk values below 1, indicating that the processes were not capable. Machine X recorded the highest defect rate of 36%, while Machine Y showed more stable performance but still below the industry standard. Based on Ishikawa diagram analysis, four main factors contributing to inaccuracy were identified: operator, machine, method, and material. The study concludes that improvements in operator training, machine maintenance, and shift standardization are necessary to enhance process stability and packaging quality. Keywords: Minitab, Process Capability, Sixpack Report, Wheat Flour